Clinical Practice Guidelines for paroxysmal supraventricular tachycardia. - Brandy Viera Valdés; Francisco De Jesús Valladares Carvajal; Félix Rolando Jorrín Román; Pablo Rodríguez Díaz (Medisur)
Clinical Practice Guidelines for paroxysmal supraventricular tachycardia. These are arrhythmias in which structures placed above the bifurcation of the bundle of His are involved; characterized by tachycardia with abrupt starting and ending. We comment its classification, common characteristics, general treatment and specific conduct for its different variables. It includes assessment guidelines focused on the most important aspects to be accomplished.